Chronic sclerosing sialadenitis: report of a rare and atypical case - Melzer, Rafaela Savio; Milani, Cintia Mussi; Sum, Fernanda Noguez; Druszcz, Rui Cesar de Bittencourt; Schussel, Juliana Lucena (ARCHIVES OF HEALTH INVESTIGATION, 2021)
A Chronic Sclerosing Sialodenitis is a rare and benign lesion that preferentially affects a submandibular gland of male patients. Although its etiology is considered unknown, it is suggested that the secretion of IgG4 immunoglobulin may be useful for its manifestation. This pathology has specific clinical characteristics for malignant neoplasms of the salivary glands, where the recommended treatment is a surgical excision. The present study presents an atypical case of chronic sclerosing sialodenitis that involves a woman’s soft palate, where there was a complete resolution of the clinical case, in which the conservative treatment was chosen by the use of medications.